Maqasid Syariah sebagai Kritik Filosofis terhadap Dominasi Murabahah dalam Perbankan Syariah Modern: Sebuah Systematic Literature Review - Afril Afril; Syukri Iska; Ahmad Lutfi (STIE Amkop Makassar, 2025)
This study aims to philosophically analyze the dominance of the murabahah financing contract in modern Islamic banking through the perspective of Maqāṣid al-Sharī‘ah using a Systematic Literature Review (SLR) approach. A total of 15 scientific articles were selected after a rigorous screening process based on thematic relevance, methodological feasibility, and full-text availability. The results indicate that the dominance of murabahah in the financing portfolio of Islamic banks is primarily driven by profitability orientation and risk-management efficiency rather than ethical and socio-economic objectives of Islamic economics. Empirical findings reveal that murabahah significantly contributes to profit generation and financial stability in Islamic banks; however, its operational practice often deviates from the substantive nature of a genuine sale contract and drifts away from the principles of justice and public welfare. Based on a maqasid analysis, current murabahah practices have not fully reflected the higher objectives of Islamic law, particularly in relation to the protection of property (ḥifẓ al-māl), justice (‘adālah), and social balance. Therefore, this research highlights the urgency of murabahah reform through a maqasid-compliance approach as the foundation for reconstructing the paradigm of Islamic economics—toward a financial system that is not only formally sharia-compliant, but also substantively aligned with social benefit and ethical well-being.